Whose accountability? A case study of NGO accountability to recipients of aid in South Sudan - Beattie, Karyn (Cranfield University, 2011)
The prominence of non-governmental organisations (NGOs) has increased dramatically in the last decade triggering concerns over the accountability of these organisations. In response, NGOs have broadened their accountability systems to include all their stakeholders, not only those who hold some form of authority over them. Particular attention has been given to ensuring accountability to the recipients of an NGO‟s assistance, known in some circles as „beneficiary accountability‟. However, the implementation of beneficiary accountability is particularly difficult in the kind of environment in which humanitarian assistance is provided – a point which is acknowledged in literature. The aim of this research was to understand the factors that influenced the implementation and the reasons for the difficulty. The case study employed qualitative methods to gather data from NGO staff and members of two Dinka communities in South Sudan. The study found that the complexity of accountability was not given sufficient consideration during implementation. Within the task-oriented environment of humanitarian aid, accountability was simplified into a set of practical steps. But while staff implemented the steps, they often missed the real essence of accountability. As a result, the mechanisms employed were not entirely appropriate for the target audience, the Dinka communities. Perhaps because of this, the community tended to prefer their own methods of holding the NGO to account. The research concludes that because of certain structural difficulties inherent in beneficiary accountability it is not only difficult, but impossible to implement within certain contexts. It is recommended that NGOs make changes to the methodology they employ when working in a context similar to the one in which the research was conducted.
Keywords: Beneficiary; accountability; Humanitarian; Accountability; Partnership; Culture; Tearfund; humanitarian aid